Authorship of scientific articles within an ethical-legal framework: quantitative model - Vallejo, Martha; BIO&OIL s.a.s., Calle100 60-04 Ofc. 211 C.C. Master Center. Bogotá, Colombia. (2012)
Determining authorship and the order of authorship in scientific papers, in modern interdisciplinary and interinstitutional science, has become complex at a legal and ethical level. Failure to define authorship before or during the research, creates subsequent problems for those considered authors of a publication or lead authors of a work, particularly so, once the project or manuscript is completed. This article proposes a quantitative and qualitative model to determine authorship within a scientific, ethical and legal frame. The principles used for the construction of this design are based on 2 criteria: a) stages of research and scientific method involving: 1. Planning and development of the research project, 2. Design and data collection, 3. Presentation of results, 4. Interpretation of results, 5. Manuscript preparation to disseminate new knowledge to the scientific community, 6. Administration and management, and b) weighting coefficients in each phase, to decide on authorship and ownership of the work. The model also considers and distinguishes whether the level and activity performed during the creation of the work and the diffusion of knowledge is an intellectual or practical contribution; this distinction both contrasts and complements the elements protected by copyright laws. The format can be applied a priori and a posteriori to the completion of a project or manuscript and can conform to any research and publication. The use of this format will quantitatively resolve: 1. The order of authorship (first author and co-author order), 2. Determine the inclusion and exclusion of contributors, taking into account ethical and legal principles, and 3. Percentages of economic rights for each authors. Descarga de material suplementario / Supplement material download(A, B, C, D)